Katarína : a novel - Winter, Kathryn (New York : Farrar Straus Giroux, 1998)
During World War II in Slovakia, a young Jewish girl in hiding becomes a devout Catholic and is sustained by her belief that she will return home to her family as soon as the war ends.
Keywords: World War, 1939-1945 -- Slovakia -- Juvenile fiction; World War, 1939-1945 -- Slovakia -- Fiction; Jews -- Slovakia -- Fiction; Orphans -- Fiction; Slovakia -- History -- 1918-1945 -- Fiction